Pubertal onset with adulthood lung function mediated by height growth in adolescence. Issue 4 (10th November 2020) - Li, Liang; Zhang, Hongmei; Holloway, John W.; Henderson, A. John; Ewart, Susan; Relton, Caroline L.; Arshad, S. Hasan; Karmaus, Wilfried
Background: Age of pubertal onset is associated with height and lung function in adulthood. It is unknown whether height growth in adolescence mediates the association of age at puberty with early adult lung function. Methods: Data from the Isle of Wight (IOW) birth cohort (n=1261) were examined in the study. Ages of pubertal events, height at ages 10 and 18 years and lung function parameters (forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1 )) at 26 years were included in a path analysis to assess the mediation effects of height growth. Findings were tested in the Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort. Results: In females in the IOW cohort, age at menarche and body hair growth showed a positive indirect association with FVC (menarche: indirect effect coefficient (IEC)=0.13, 95% CI 0.05–0.20, p=1.28×10 −3 ; body hair growth: IEC=0.08, 95% CI 0.01–0.15, p=0.017) and FEV1 (menarche: IEC=0.09, 95% CI 0.01–0.17, p=0.028; body hair growth: IEC=0.07, 95% CI 0.01–0.14, p=0.043) at 26 years through height growth and lung function at 18 years. In males, age at body hair growth (IEC=0.08; 95% CI 0.01–0.15, p=0.047), growth spurt (IEC=0.09; 95% CI 0.01–0.17, p=0.034) and facial hair growth (IEC=0.09; 95% CI 0.02–0.16, p=0.014) had positive indirect effects on FVC at 26 years, but voice deepening did not show statistically significant indirect effects (p>0.05). For pubertal events available in the ALSPAC cohort, results consistent with the IOW cohort were found for both females and males. Conclusion: Effects of age of puberty on FVC in early adulthood are likely mediated by height growth during adolescence. Height growth in adolescence mediates the association of age of pubertal onset with FVC in young adults. For females, such mediation effects are also identified for FEV1 . https://bit.ly/3mwSTi6